Національні природні ядра екомережі Вінницької області - Яцентюк, Ю.В. (Український географічний журнал, 2011)
Рассмотрены национальные природные ядра экосети Винницкой области, особенности их биотического и ландшафт-ного разнообразия. Выделены существующие и перспективные биоцентры национальных природных ядер области. The national core areas of econetwork of Vinnytsya oblast, the features of their biotic and landscape diversity are considered. The existent and prospective biocentres of the national core areas in Vinnytsya oblast are defined.